A preliminary study into impression management practices in chairman’s statements in South African annual reports - Yaeesh Yasseen; Mahdiyyah Moola-Yasseen; Nirupa Padia (Communicare)
The purpose of this study was to determine whether there is a systematic difference in the textual characteristics of information in the chairman’s statement of profitable and unprofitable companies on the JSE main board. The study replicated research by Clatworthy and Jones (2006) to determine the existence of impression management within chairman’s statements. The difference in reporting between profitable and unprofitable companies was analysed in relation to three pre-determined textual characteristics using an attribution theory perspective. The primary conclusion drawn is that impression management does exist in the chairman’s statements of companies listed on the JSE main board. Another finding of the study was that ‘extremely unprofitable’ companies are less likely to employ impression management. The findings indicate that users of annual reports should be alert to the existence of reporting bias introduced by management and its impact on the usefulness of management commentary in their decision-making.